2008
DOI: 10.1117/1.2967909
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of hexyl 5-aminolevulinate-induced photodynamic therapy in rat bladder cancer by optical spectroscopy

Abstract: Monitoring of the tissue response to photodynamic therapy (PDT) can provide important information to help optimize treatment variables such as drug and light dose, and possibly predict treatment outcome. A urinary bladder cancer cell line (AY-27) was used to induce orthotopic transitional cell carcinomas (TCC) in female Fischer rats, and hexyl 5-aminolevulinate (HAL, 8 mM, 1 h)-induced PDT was performed on day 14 after instillation of the cancer cells (20 J/cm(2) fluence at 635 nm). In vivo optical reflectance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…In an earlier investigation, Larsen et al . had found met‐Hb formation in a rat bladder tumor model, in which some of the animals the relative contribution to overall oxy‐Hb was up to 40% after 5‐ALA‐based PDT. Interestingly, met‐Hb has a broad absorption peak at ca.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier investigation, Larsen et al . had found met‐Hb formation in a rat bladder tumor model, in which some of the animals the relative contribution to overall oxy‐Hb was up to 40% after 5‐ALA‐based PDT. Interestingly, met‐Hb has a broad absorption peak at ca.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse optical spectroscopy (DOS) can be used to probe biological tissue for its optical properties such as absorption and scattering coefficients. DOS has been used to measure the tissue oxygenated hemoglobin (HbO 2 ), deoxygenated hemoglobin (Hb), total hemoglobin concentration (THC), and oxygen saturation (StO 2 ) levels of PDT-treated tumors [2830, 32]. Diffuse correlation spectroscopy (DCS) allows us to measure the relative blood flow (rBF) in a tumor by using the autocorrelation function of fluctuating light intensities to calculate the average flow rate of scattering particles [2829, 33].…”
Section: Introductionmentioning
confidence: 99%
“…6). The cell line AY27 is an appropriate model for PDT study of bladder cancer, shown by previous studies, using hexylaminolevulinate (HAL) [33,39] and photochemical internalization (PCI) (see Ref. [40]).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies also play an important role in this aspect [32]. Investigations on bladdercancer cell lines is a natural first step to determine the properties of newly developed drugs and to test various treatment strategies [6,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%